The two faces of tumor-associated macrophages and their clinical significance in colorectal cancer - Pinto, Marta L. (2019)
© 2019 Pinto, Rios, Durães, Ribeiro, Machado, Mantovani, Barbosa, Carneiro and Oliveira. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY). The use, distribution or reproduction in other forums is permitted, provided the original author(s) and the copyright owner(s) are credited and that the original publication in this journal is cited, in accordance with accepted academic practice. No use, distribution or reproduction is permitted which does not comply with these terms.